Clinical outcome after thrombectomy in patients with stroke with premorbid modified rankin scale scores of 3 and 4: a cohort study with 136 patients - Seker, Fatih; Pfaff, Johannes; Schönenberger, Silvia; Herweh, Christian; Nagel, Simon; Ringleb, Peter A.; Bendszus, Martin; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2019)
BACKGROUND AND PURPOSE: We aimed to analyze the clinical outcome after mechanical thrombectomy in patients with premorbid mRS 3 and 4 because there are currently no data on this patient group. - MATERIALS AND METHODS: Between January 2009 and November 2017, all patients with premorbid mRS 3 or 4 undergoing mechanical thrombectomy due to anterior circulation stroke were selected. Good outcome was defined as a clinical recovery to the status before stroke onset (ie, equal premorbid mRS and mRS at 90 days). In addition, mortality at discharge and at 90 days was analyzed. - RESULTS: One hundred thirty-six patients were included, of whom 81.6% presented with premorbid mRS 3; and 18.4%, with premorbid mRS 4; 24.0% of patients with premorbid mRS 4 achieved clinical recovery compared with 20.7% of patients with premorbid mRS 3 (P = .788). However, the proportion of hospital mortality and mortality at 90 days was nonsignificant, but markedly higher in patients with premorbid mRS 4. Multivariate analysis identified low NIHSS scores (OR, 0.92; 95% CI, 0.85-0.99; P = .040), high ASPECTS (OR, 1.45; 95% CI, 1.02-2.16; P = .049), and TICI 2b-3 (OR, 7.11; 95% CI, 1.73-49.90; P = .017) as independent predictors of good outcome. - CONCLUSIONS: Good outcome in patients with premorbid mRS 3 and 4 is less frequent compared with premorbid mRS 0-2. Nevertheless, about 20% of the patients return to their premorbid mRS, which may justify endovascular treatment. The most important predictor of good outcome is successful recanalization.